Study of Floods and Drainage Management in Sukawati District - Suryanti, Irma; Indah Dianti Putri, Putu (Fakultas Teknik, Universitas Brawijaya, 2026)
The Sukawati District experiences frequent flooding during the rainy season due to the drainage canals’ inability to handle peak flood discharge. The canals’ insufficient capacity, compounded by sediment and garbage accumulation, results in water overflowing the canals’ freeboards. This study aims to characterize the inundation and drainage issues in Sukawati District. Both primary and secondary data are utilized for analysis. The methodology includes field surveys, identification of inundation and flood-prone areas, inventory of the existing drainage system, hydrological and hydraulic analysis, and drainage network planning. The findings reveal 38 inundation sites within Sukawati District, with inundation durations ranging from 50 minutes to 24 hours. The inundation depth ranges from 15 to 200 cm, and the frequency of occurrence ranges from 1 to 10 times per year. The prioritization of drainage management is based on flooding characteristics, economic losses, social disturbances, impacts on government facilities, transportation disruptions, and damage to residential areas. Recommendations include normalizing the existing canals using appropriately sized river stone pairs to enhance water discharge capacity, particularly during rainy periods.